Stay or stray? Evidence for alternative mating strategy phenotypes in both men and women - Wlodarski, Rafael (Biol Lett, 2015)
In all comparative analyses, humans always fall on the borderline between obligate monogamy and polygamy. Here, we use behavioural indices (sociosexuality) and anatomical indices (prenatal testosterone exposure indexed by 2D : 4D digit ratio) from three human populations to show that this may be because there are two distinct phenotypes in both sexes. While males are more promiscuous and display higher prenatal testosterone exposure than females overall, our analyses also suggest that the within-sex variation of these variables is best described by two underlying mixture models, suggesting the presence of two phenotypes with a monogamous/promiscuous ratio that slightly favours monogamy in females and promiscuity in males. The presence of two phenotypes implies that mating strategy might be under complex frequency-dependent selection.